DESAIN PROGRAM SIMULASI UNJUK KERJA KODE LARGE KASAMI PADA SISTEM KOMUNIKASI DIRECT SQUENCE SPREAD SPECTRUM MELALUI KANAL MULTIPATH FADING - Widi Arjana Yasa, I Ketut; Pramaita, Nyoman; Ary Esta Dewi Wirastuti, Ni Made (Jurnal SPEKTRUM, 2021)
Selection of Pseudo Noise (PN) code in CDMA multiple access is needed to overcome problems related to interference. In this study, we simulate the large kasami code with the aim of knowing the performance of the large kasami code on flat fading channels and frequency selective fading channels with variations in the number of multipath components. The receiver system uses a correlation receiver to correlate the code used by each user. The simulation results from the performance of the large kasami code through the flat fading channel show that the simulation carried out is valid, where the simulation BER value is close to the flat theoretical BER value. The frequency selective fading channel shows different BER values from variations in the number of multipath components, where the multipath 60 component produces the worst BER value. Auto correlation code large kasami has a value when the time is not equal to zero which can interfere with the desired signal and there is a cross-correlation signal level value that will interfere with each other's users.